Pengaruh orientasi keusahawanan dan organisasi pembelajaran terhadap prestasi perusahaan kecil dan sederhana sektor pembuatan - Mohamad Rozi, Hassan (2017)
Small and Medium Enterprises (SME) contributes substantially to the national development especially in Gross Domestic Product (GDP), employment and exports. However, globalisation causes the SME to withstand the challenges and should elevate the performance in order to stay competitive. Thus, several factors that influenced the performance of SME in the manufacturing sector are identified in order to develop the research framework. Specifically, the objectives of this study are to empirically examine the relationships among the factors i.e. entrepreneurial orientation, learning organisation competing strategy and the SME performance. Data collection through survey has been employed through convenience sampling that was conducted on the SME manufacturing company registered with the SME Corporation, Ministry of International Trade and Industry (MITI). 135 questionnaires were successfully collected and returned for analysis. Multivariate statistical technique through multiple linear regression was used to analyse the hypothesised relationship in the research framework. The findings revealed that the impact of entrepreneurial orientation, learning organization and competing strategy on SME performance are significantly positive at p < 0.05 (two-tailed) respectively. Also, the relationship between entrepreneurial orientation and learning organisation to competitive strategies are found to be positively significant at p < 0.05 (two-tailed). From the analysis, it also showed that the competing strategy mediates the relationship between the entrepreneurial orientation and learning organisation on SME performance. In conclusion, the findings of this study are very important for the SMEs especially in the manufacturing industry to consider all variables under study to remain competitive in the rapidly dynamic changing business environment.